Kinematics of base sphere as a segment of spheres kinematical chain: Gravitational acceleration as equivalent central acceleration - Živanović Milovan D.; Živanović Miloš M. (FME Transactions, 2013)
Assuming that the theory for differential geometry of curve is correct, this paper introduces a spheres kinematical chain of changeable radii positioned in such a fashion that the centre of the next sphere is firmly attached to the previous one within the chain. The kinematical chain consists of the base sphere and the rest of the chain which is inside the base sphere. The paper discusses the undisturbed and disturbed motion of the base sphere. The gravitational acceleration is interpreted as equivalent central acceleration during undisturbed rotation of the base sphere. The disturbed motion with respect to the undisturbed motion is described by increments of corresponding kinematical quantities. The relationship with the existing laws for translational motion in the classical mechanics is also established. And finally, a simple experiment for verification of the exposed theory is proposed in this paper.